1987
DOI: 10.1149/1.2100403
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Photoresist Planarization Properties by Thermal Cure: Role of the PAC

Abstract: Photoresist planarization properties are shown to be improved by a subsequent thermal cure. In order to understand the effects of thermal processing on photoresists, this paper discusses their thermal chemistry in relation to their thermal flow properties. The photoactive compound (PAC) is shown to hinder the thermal flow of the photoresist by ester‐linkage up to the temperature where the resin undergoes complete thermal cross‐linking. Transformation of the PAC by a suitable exposure to UV light will let the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As is demonstrated in Fig. 26 A ood exposure with a specic dosage in ambient atmosphere before reow is adequate to transform some portion of PAC to indene carboxylic acid and hence facilitates the reowing process. We attribute this phenomenon to the complex chemical reactions of the photoresist materials with the UV light.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As is demonstrated in Fig. 26 A ood exposure with a specic dosage in ambient atmosphere before reow is adequate to transform some portion of PAC to indene carboxylic acid and hence facilitates the reowing process. We attribute this phenomenon to the complex chemical reactions of the photoresist materials with the UV light.…”
Section: Resultsmentioning
confidence: 97%
“…25 The formation of ester-linkage, which gives rise to some degree of crosslinking, can hinder the resin from reowing to its own limit. 26 A ood exposure with a specic dosage in ambient atmosphere before reow is adequate to transform some portion of PAC to indene carboxylic acid and hence facilitates the reowing process. It is found that although the ood exposure helps to reduce the dips, a spherical lens shape still cannot be formed even using a high ood exposure dosage.…”
Section: Resultsmentioning
confidence: 99%
“…15,18 Thus, planarization enhancement during baking occurs only locally, typically over a range of about 10 pm. 13 Polyimides may also undergo these reactions during baking (curing).…”
Section: Spin Coating and Planarizationmentioning
confidence: 99%
“…More importantly, these films typically shrink by large amounts during the curing process which degrades any planarization that may have occurred due to thermal flow.8111, 14,15 Thus, commerical positive photoresists and polyimides are poor choices as planarizing materials when high degrees of planarization over large spatial areas (> 50 um) are required.…”
Section: Spin Coating and Planarizationmentioning
confidence: 99%
“…Several planarization investigations on sub-micron patterned substrate have been reported [3]- [13] . In these literatures, influences of processes such as pattern/feature size, spin speed for material coating, and film thickness for planarization were mainly discussed and the discussion about the effect of material properties such as solution viscosity for planarization was not so detailed [4], [6], [9] . Recently, some reports which focused on new materials to obtain a good planarization surface by spin coating of the materials on a topo-patterned substrate have been disclosed [14], [15] .…”
Section: Introductionmentioning
confidence: 99%